Prenatal tobacco exposure and self-regulation in early childhood: Implications for developmental psychopathology. (6th May 2015) - Cicchetti, Dante; Wiebe, Sandra A.; Clark, Caron A. C.; De Jong, Desiree M.; Chevalier, Nicolas; Espy, Kimberly Andrews; Wakschlag, Lauren
Abstract Prenatal tobacco exposure (PTE) has a well-documented association with disruptive behavior in childhood, but the neurocognitive effects of exposure that underlie this link are not sufficiently understood. The present study was designed to address this gap, through longitudinal follow-up in early childhood of a prospectively enrolled cohort with well-characterized prenatal exposure. Three-year-old children (n = 151) were assessed using a developmentally sensitive battery capturing both cognitive and motivational aspects of self-regulation. PTE was related to motivational self-regulation, where children had to delay approach to attractive rewards, but not cognitive self-regulation, where children had to hold information in mind and inhibit prepotent motor responses. Furthermore, PTE predicted motivational self-regulation more strongly in boys than in girls, and when propensity scores were covaried to control for confounding risk factors, the effect of PTE on motivational self-regulation was significant only in boys. These findings suggest that PTE's impact on neurodevelopment may be greater in boys than in girls, perhaps reflecting vulnerability in neural circuits that subserve reward sensitivity and emotion regulation, and may also help to explain why PTE is more consistently related to disruptive behavior disorders than attention problems.